(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article deals with the great afford of poet-translators who investigated turkic literature, mainly by the works of Sergei Nikolaevich Ivanov, who made enormous contribution to the development of art of translation . S.N. Ivanov was one of the researchers who did the translation of the works of great Turkic poet . Sergei Nikolaevich Ivanov let people to know the original meaning of Alisher Navoi’s aphorisms and sayings.